2006
DOI: 10.1007/s00436-006-0164-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cryptosporidium subtypes in humans and domestic and wild ruminants in Portugal

Abstract: To investigate the transmission of cryptosporidiosis in Portugal, Cryptosporidium hominis and Cryptosporidium parvum from HIV-infected patients, cattle, and wild ruminants were characterized by sequence analysis of the 60-kDa glycoprotein (GP60) gene. Fourteen subtypes within nine subtype families were identified, and three of the subtype families (If, IIb, and IId) were restricted or largely limited to Portugal. Parasites from cattle from various regions in Portugal and wild ruminants in Lisbon showed limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
146
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(186 citation statements)
references
References 24 publications
32
146
2
2
Order By: Relevance
“…13 . Amerika Birleşik Devletleri' nde buzağılarda zoonotik olan IIa subtip familyası ile buna bağlı altı subtip tespit edilmiş ve yaygın olan subtipin ise IIaA15G2R1 olduğu bildirilmiştir 4,12 .…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation
“…13 . Amerika Birleşik Devletleri' nde buzağılarda zoonotik olan IIa subtip familyası ile buna bağlı altı subtip tespit edilmiş ve yaygın olan subtipin ise IIaA15G2R1 olduğu bildirilmiştir 4,12 .…”
Section: Tartişma Ve Sonuçunclassified
“…Dünyada sığırlarda Cryptosporidium türlerinin moleküler karakterizasyonu çeşitli ülkelerde yapılmış ve C. parvum IIaA15G2R1, IIaA16G1R1, IIaA16G3R1, IIaA18G3R1 ve IIdA15G1 subtipleri belirlenmiştir 4,[7][8][9][10][11][12] . Bunlardan C. parvum IIaA15G2R1 subtipi hem insan ve hemde sığırlar-da bildirilmiştir 13,14 .…”
unclassified
“…This subgenotype has been reported in humans, including a child with diarrhea from India, and could potentially be zoonotically transmitted. 12,19 Interestingly, a study from Spain has reported that the IId subtype is more common in goat kids than any other subgenotype. 20 The C. hominis isolate that could not be genotyped was confirmed by sequencing the SSU ribosomal RNA PCR product (Genbank accession no.…”
mentioning
confidence: 99%
“…In fact, this variant is frequently observed in C. parvum populations worldwide and has been widely reported in zoonotic infections. 1 As a risk factor for human cryptosporidiosis, contact with cattle was implicated in the neighboring countries, such as Egypt and Spain, 4,19 as well as the United States, United Kingdom, Ireland, and Australia. [20][21][22][23] However, in our study, taking into account the age of children and their kind of life (human settlement), contact with livestock is possible; however, drinking raw (unpasteurized) milk may also represent a probable risk factor for Cryptosporidium transmission in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Subgenotyping of C. parvum isolates was performed using nested PCR to amplify a fragment of the gp60 gene as described elsewhere. 1,7 Briefly, two-step nested PCR was used. AL3531 (5 -ATAGTCTCCGCTGTATTC-3 ) and AL3535 (5 -GGA AGGAACGATGTATCT-3 ) primers were used for the firstround PCR and AL3532 (5 -TCCGCTGTATTCTCAGCC-3 ) and AL3534 (5 -GCAGAACCAGCATC-3 ) primers were used for the second-round PCR to amplify a 840-bp fragment.…”
Section: Methodsmentioning
confidence: 99%